The five people you meet in heaven - Albom, Mitch, 1958- (New York : Hyperion, 2003)
Weaves three stories about 83-year-old Eddie, the head maintenance person at Ruby Point Amusement park. Eddie meets 5 individuals in heaven each with a story to share, a secret to reveal and a lesson. The have profound meanings for Eddie on the real purpose of his life.
Keywords: Accident victims -- Fiction; Amusement parks -- Fiction; Amusement rides -- Fiction; Future life -- Fiction; Older men -- Fiction; Heaven -- Fiction; Death -- Fiction; Psychological fiction